2021
DOI: 10.3389/frph.2021.692249
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Extrapelvic Endometriosis in the Medial Thigh

Abstract: Extrapelvic endometriosis, although rare, can present in the musculoskeletal system of reproductive-age women and cause significant pain and morbidity. The pathophysiology of this disease is not well understood. In this study, we described the case of a 39-year-old women with an inner-thigh mass causing catamenial pain. Core-biopsy of the mass confirmed endometriosis and she was referred to minimally-invasive gynecology for management. Surgical excision was performed by a multidisciplinary team and she remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Intestinal endometriosis refers to the infiltration of endometrial glands and stroma from the plasma layer of the intestinal canal to at least the subplasma adipose tissue, whereas colorectal endometriosis is often located in the subplasma and intrinsic muscular layer, with possible involvement of the submucosal layer, but lesions involving the mucosal layer are relatively rare [5]. The exact prevalence is not known, but some retrospective studies have shown that intestinal involvement in patients with endometriosis ranges from 5.3% to 12%, with the sigmoid colon and rectum being the most frequently involved sites in the GI tract [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], accounting for 50%-70% [29]. Also in general, ectopic endometrial tissue in the rectum is usually located in the muscular layer and rarely in the submucosa, and the rectal mucosa is usually not involved [30].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal endometriosis refers to the infiltration of endometrial glands and stroma from the plasma layer of the intestinal canal to at least the subplasma adipose tissue, whereas colorectal endometriosis is often located in the subplasma and intrinsic muscular layer, with possible involvement of the submucosal layer, but lesions involving the mucosal layer are relatively rare [5]. The exact prevalence is not known, but some retrospective studies have shown that intestinal involvement in patients with endometriosis ranges from 5.3% to 12%, with the sigmoid colon and rectum being the most frequently involved sites in the GI tract [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], accounting for 50%-70% [29]. Also in general, ectopic endometrial tissue in the rectum is usually located in the muscular layer and rarely in the submucosa, and the rectal mucosa is usually not involved [30].…”
Section: Discussionmentioning
confidence: 99%